Potential influence of geomagnetic activity on blood pressure statistical fluctuations at mid-magnetic latitudes - Pengzhi He; Chen Li; Minlan Xu; Ruilong Guo; Alexander William Degeling; Timo Pitkänen; Yude Bu; Xiangyun Zheng; Yue Zhang; Xianghong Jia; Anmin Tian; Chenyao Han; et al. (Communications Medicine)
Abstract Background Solar activity and the consequent geomagnetic activity (GMA) profoundly influence human biological rhythms and cardiovascular system functions. Although the response of blood pressure (BP) to GMA has attracted considerable attention, it is unclear whether the GMA can have an influence alone and how it occurs. Methods In this six-year time series analysis, we collated over 500,000 BP measurements from two representative cities (Qingdao and Weihai) at mid-magnetic latitudes in China. Using various statistical methods, we analyzed the correlation between BP and the GMA (represented by Ap index) and their quasi-periodic fluctuations. Additionally, we conducted a comparative analysis of the influence of other environmental factors (air temperature and PM2.5) on BP. Results The statistical BP level fluctuations correlate with the GMA. Both BP and the GMA index exhibit similar annual bimodal patterns and multiple periodicities, including 12-month and 6-month cycles, and an intermittent 3-month cycle. In contrast, other known environmental factors influencing BP such as air temperature and PM2.5 do not exhibit similar periodicities, particularly they lack 3-month cycles. In years with higher GMA levels, the BP shows stronger correlations with the Ap index and responds on a shorter timescale. Additionally, BP in females appears to be more strongly correlated with GMA. Conclusions Our findings highlight potential risks to individuals with hypertension with elevated GMA levels, deepen our understanding of GMA’s role in human health, and offer insights for healthcare policymakers on the clinical significance of the geomagnetic environment.